Allylation and propargylation of aldehydes mediated by in situ generated zinc from the redox couple of Al and ZnCl2 in 2N HCl - Mondal, Bibhas; Adhikari, Utpal; Hajra, Partha Pratim; Roy, Ujjal Kanti (New journal of chemistry, 2021)
A simple one pot allylation and propargylation of aldehydes mediated by zinc(0), which is in situ generated from the redox couple of Al and ZnCl2 in 2N HCl, is demonstrated to afford the corresponding homoallyl and homopropargyl alcohols with excellent yields.